In Pursuit of “Islamic Art and Architecture” - Tammy Gaber (International Institute of Islamic Thought, 2009)
Books Reviewed: Richard Yeomans. The Art and Architecture of Islamic Cairo. United Kingdom: Garnet Publishing, 2006; Doris Behrens-Aboseif. Cairo of the Mamluks: A History of the Architecture and Its Culture. United Kingdom: I.B. Tauris, 2007. GeorgeMichell. The Majesty ofMughalDecoration: The Art and Architecture of Islamic India. New York: Thames and Hudson, 2007. Many people take it for granted that the blanket term Islamic art and architecture is sufficient to convey the vast production carried out in the name of Islam; however, they often have a limited vision of what this term actually entails. Islam’s time span (fourteen centuries and counting) and geography (historically ranging from Spain to China) simply means that the art and architecture produced in its name deserves a more detailed and accountable presentation of fact. In other words, it would be unthinkable for scholars to use a term like Christian art and architecture instead of such specific terms as Byzantine, Romanesque, and Gothic, each of which relates to a specific time and place. Thus, the vocabulary of understanding the production of art and architecture in Islam’s name requires the use and understanding of clear terms and deserves specific publication and study ...